(untitled) (Research, Society and Development, 2020)
Agricultural cooperatives contribute to rural development in different ways in the regions in which they operate. To guarantee such contributions, they use some strategies, among them, business diversification, which can be classified into concentric strategies and conglomerate strategies. To this end, this article aims to point out the existing businesses in agricultural cooperatives in Rio Grande do Sul, through the analysis of diversification. Concentric diversification is defined as that in which the new business area of the organization is directly related to existing businesses. In turn, conglomerate diversification is defined with the business area with little or no relation to the business areas previously performed by the organization, whether in the technological or commercial aspect. To detail the business strategies of agricultural cooperatives with respect to the types of diversification, surveys were conducted in 17 agricultural cooperatives in the northern half of the state of Rio Grande do Sul. As a result, it was found that, considering diversification classified as concentric, types of business are related to the agro-industrialization of grains resulting from the production of members, especially rice, beans, wheat and corn, in addition to other by-products intended for animal nutrition, such as bran and feed. With regard to conglomerate diversification, the cooperatives have supermarkets aimed at meeting the demand of members and the community in general, an input store for the sale of products for agriculture and livestock, appliance stores, agricultural machinery, clothing and building materials, gas station, pharmacies, among others. This diversification of business present in the cooperatives, in addition to expanding their insertion in the markets, makes it possible to maintain the interaction between members and the community in general.